Efficacy and safety of elotuzumab for the treatment of multiple myeloma - Gavriatopoulou, M.; Terpos, E.; Kastritis, E.; Dimopoulos, M.A. (Expert Opinion on Drug Safety, 2017)
Introduction: Multiple myeloma (MM) is the second most common hematologic malignancy and despite significant outcome improvements with novel agents, the majority of patients will eventually relapse and develop treatment resistance. Immunotherapy is emerging as a promising therapeutic approach in MM. Areas covered: Elotuzumab is a monoclonal antibody directly targeting the SLAMF7 receptor, expressed on normal and malignant plasma cells. Elotuzumab has no meaningful antimyeloma activity when given as monotherapy to patients with relapsed or refractory MM (RRMM). However, it demonstrated significant antimyeloma activity in preclinical studies and when it is combined with other antimyeloma agents (i.e. bortezomib or lenalidomide) in clinical trials, it improved response and clinical outcomes with no additive toxicity. This review provides a brief description of the elotuzumab mechanism of action and an overview on its efficacy in preclinical and clinical trials, including its safety and toxicity profile. Expert commentary: Based on the results of a phase 3 clinical trial (ELOQUENT-2), which compared lenalidomide and dexamethasone with or without elotuzumab in patients with RRMM, elotuzumab was approved by FDA in November 2015 for MM patients who received 1–3 prior lines of therapy. Studies with combinations of elotuzumab with other anti-myeloma drugs in different phases of MM are ongoing. © 2017 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: CS1; Elotuzumab; monoclonal antibody; multiple myeloma; SLAMF7